Experimental Study On Clay Stabilization With Waste Limestone From Marble Industri - A. B. Muhiddin; T. Harianto; A. Arsyad; Indrayanti . (International Association of Lowland Technology, 2019)
In this research, chemical stabilization on clay soils was performed using waste limestone powder from marble industry and acrylic acid. The research was aimed to analyze the characteristics of waste marble, to analyze clay strength before and after stabilized with waste marble powder, to analyze the effect of acrylic acid as activator in clay stabilization using waste marble, and finally to study the microstructure of soil stabilized by marble powder and acrylic acid solution. Laboratory tests were performed by mixing marble powder in the amount of 5%30% of clay and with addition of acrylic acid solution as much as 5%-15% of water mixed. For soil microstructure study, SEM and XRD tests were conducted. Clay mixture with 20%-30% of marble powder increased CBR value to more than 6%. Addition of acrylic acid solution with optimum content of marble powder with 3- and 7-day curing increased the value of UCS to medium consistency. Marble powder contains dominantly of CaO compound of 97.15% which is an effective material for clay soil stabilization. These results show that the mixture of clay with marble powder and acrylic acid as stabilization agents could increase soil bearing capacity for road subgrade layer.